The Transfer Of Productive Land For Industrial Interest - Asep Hermawan (Jurnal Daulat Hukum, 2021)
This study aims to analyze & study the regulation of the practice of converting productive land into industrial land which often occurs in regions as the regional economy advances. The research uses a sociological juridical approach. Based on the research it was concluded that not all of the conversion of agricultural land to industrial areas can balance the food sector with the industrial sector. Act No. 5 of 1960 concerning Basic Agrarian Regulations, Act No. 41 of 2009 concerning Protection of Agricultural Land for Sustainable Food, & Government Regulation no. 1 of 2011 concerning the Determination & Transfer of Agricultural Land for Sustainable Food has clearly stated that the conversion of productive land can only be carried out for the public interest so that industrial interests are the exception, so that the regulation can balance the food sector.